2020
DOI: 10.1017/s1047951120000591
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of paediatric cardiac patients after 30 minutes of cardiopulmonary resuscitation prior to extracorporeal support

Abstract: Objectives:To characterise the mortality and neurological outcomes of paediatric cardiac patients requiring cardiopulmonary resuscitation for more than 30 minutes prior to extracorporeal membrane oxygenation cannulation and to identify risk factors associated with adverse outcomes in this population.Materials and methods:Observational retrospective cohort study in paediatric cardiac patients undergoing cardiopulmonary resuscitation for greater than 30 minutes prior to cannulation in a tertiary children’s hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 37 publications
(127 reference statements)
2
19
0
1
Order By: Relevance
“…Pilar et al found that E-CPR longer than 50 minutes predicted the fatal outcome. They, however, described three patients who survived very long CPR episodes (118, 134, and 139 min) with mild neurological deficits, similar to the results of our study (15). This findings indicate that survival without neurological impairment can be expected even in CPR lasting more than one hour.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Pilar et al found that E-CPR longer than 50 minutes predicted the fatal outcome. They, however, described three patients who survived very long CPR episodes (118, 134, and 139 min) with mild neurological deficits, similar to the results of our study (15). This findings indicate that survival without neurological impairment can be expected even in CPR lasting more than one hour.…”
Section: Discussionsupporting
confidence: 91%
“…All of them survived without neurological impairment. It is a subject to discussion whether therapeutic hypothermia can improve the neurological outcome after CPR ( 15 ). None of our 16 E-CPR patients underwent therapeutic hypothermia, but hyperthermia was agressively treated.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations